“I’ll See U Later”: SELF-EFFICACY DAN PROKRASTINASI AKADEMIK PADA MAHASISWA PSIKOLOGI UNIVERSITAS INFORMATIKA DAN BISNIS INDONESIA - Dewi Arpi Pratami; Vika Fatimatuzzahra Azzali; Nida Muthi Annisa (LPPM UNIBI, 2020)
Students certainly cannot be separated from academic and non-academic assignments. The tasks are faced by students can not be separated from the number and burden of courses taken. This makes students feel tired and have trouble dividing time. This phenomenon occurs in faculty students psychology University of Informatics and Business Indonesia level 2 and 3. Some psychology students level 2 and 3 have done academic procrastination because they felt unable and not sure to complete the course assignments taken. This research aims to see whether there is a relationship of Self-Efficacy with Academic Procrastination on students Psychology of the University of Informatics and Business Indonesia. The method used in this study is a correlational quantitative method. The sampling of this research used technique Accidental Sampling at the level 2 and 3 psychology faculty students Indonesian Business (N = 50). This study uses two types of scales, namely the self-efficacy scale (35 items valid, ) and academic scale procrastination (36 valid items, .). Data analysis using techniques Pearson Product Moment Correlation with the help of IBM SPSS Statistics 25 Version for Windows. Results The analysis shows that there is no relationship of self-efficacy with academic procrastination (p = 0.063 with p> 0.05) in the students of the psychology faculty level 2 and 3, University of Informatics and Indonesian business. The results of the study were not signi¦cant of possible due to other factors being has more influence on academic procrastination. Among them are academic motivation andself regulation